Masculine and Feminine Personal Determinatives before Women’s Names at Nuzi: A Gender Indicator of Social or Economic Independence? - Abrahami, Philippe
http://cdli.ucla.edu/pubs/cdlb/2011/cdlb 2011_ 001.html